2022
DOI: 10.1038/s41612-022-00273-3
|View full text |Cite
|
Sign up to set email alerts
|

A diurnal story of Δ17O($$\rm{NO}_{3}^{-}$$) in urban Nanjing and its implication for nitrate aerosol formation

Abstract: Inorganic nitrate production is critical in atmospheric chemistry that reflects the oxidation capacity and the acidity of the atmosphere. Here we use the oxygen anomaly of nitrate (Δ17O($$\rm{NO}_{3}^{-}$$ NO 3 − )) in high-time-resolved (3 h) aerosols to explore the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 88 publications
3
24
0
Order By: Relevance
“…This phenomenon revealed the enhanced photochemical capabilities of atmosphere and the less importance of heterogeneous reactions in the fresh nitrate production when the air pollutants were cleaned by the rain, which was supported by the previous study of oxygen isotopes of nitrate in precipitation (Y.‐L. Zhang et al., 2022).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This phenomenon revealed the enhanced photochemical capabilities of atmosphere and the less importance of heterogeneous reactions in the fresh nitrate production when the air pollutants were cleaned by the rain, which was supported by the previous study of oxygen isotopes of nitrate in precipitation (Y.‐L. Zhang et al., 2022).…”
Section: Discussionsupporting
confidence: 72%
“…Meanwhile, O 3 increased to 20.7 ppb and the ALWC was extremely low (4.9 μg m −3 ; Figure 1d and Figure S5 in Supporting Information S1). This phenomenon revealed the enhanced photochemical capabilities of atmosphere and the less importance of heterogeneous reactions in the fresh nitrate production when the air pollutants were cleaned by the rain, which was supported by the previous study of oxygen isotopes of nitrate in precipitation (Y.-L. Zhang et al, 2022). In summer, the high values of Δ 17 O-NO 3 − (>30‰) were found on 17 and 24 August (Figure 1b), indicating the high contribution of NO 2 + HC/H 2 O pathway.…”
Section: Influence Factors Of Nitrate Productionsupporting
confidence: 71%
“…Over the years, numerous studies around the world have observed δ 15 N of p NO 3 – and used the data set to identify the emission sources of atmospheric NO x in different regions. However, even in the most densely sampled region like Beijing, δ 15 N­(NO 3 – ) records still remain spatially fragmented. This makes it difficult to understand the vertical distribution of nitrate sources from the ground surface to high altitudes, as nitrate aerosols are influenced by emissions, meteorology, and transport.…”
Section: Introductionmentioning
confidence: 99%
“…With the weakening of gas‐particle distribution, the main formation mechanism of NO 3 − in winter daytime was the photochemical formation (NO 2 + OH/H 2 O), the contribution of which showed the highest increase around noon with 48% (Sun et al., 2013; Zhang et al., 2022). While the nocturnal chemistry (NO 3 + HC/H 2 O and N 2 O 5 + H 2 O/Cl − ) in the haze night suggested the dominance and the contribution peaked at midnight with an increase even of 72% (Zhang et al., 2022). In contrast, the high level of sulfate (7.4 ± 3.8 μg m −3 ; from 2.2 to 20.3 μg m −3 ) in winter was mainly observed during severe haze events with high humidity (85.1%–97.3%) (Figure S11 in Supporting Information ).…”
Section: Resultsmentioning
confidence: 99%
“…The ambient temperature in this study fluctuated between −5°C and 5°C and was relatively constant between different RH values, which made the NO 3 − be readily concentrated in the particle phase. With the weakening of gas‐particle distribution, the main formation mechanism of NO 3 − in winter daytime was the photochemical formation (NO 2 + OH/H 2 O), the contribution of which showed the highest increase around noon with 48% (Sun et al., 2013; Zhang et al., 2022). While the nocturnal chemistry (NO 3 + HC/H 2 O and N 2 O 5 + H 2 O/Cl − ) in the haze night suggested the dominance and the contribution peaked at midnight with an increase even of 72% (Zhang et al., 2022).…”
Section: Resultsmentioning
confidence: 99%